The stabilising impacts of corruption in Nepal's post-conflict transition. Issue 1 (2nd January 2020) - Jarvis, Tom
ABSTRACT: The peace-building literature widely frames corruption as a threat to the stability of states transitioning from armed conflict. Underlying this framing are liberal assumptions on the institutions required for long-term stability, to which corruption is seen as necessarily detrimental. In this article, I add to an emergent literature critical of this framing by examining the long-term impacts of corruption on local-level stability in Ghorahi, Nepal. Drawing on a new dataset of 89 interviews, I demonstrate the stabilising consequences of corruption on two key aspects of Nepal's post-2006 transition. First, I show that elite-level corruption arising from the transformation of the Maoist insurgency into the political mainstream has inadvertently contributed to the social reintegration of rank and file ex-combatants. Second, I show how a corrupt elite network in local government contributed to the cooperation between political parties – including the emerging post-conflict Maoist party. These elements broaden the evidence for the stabilising consequences of corruption, which is largely focused on the effects of elite-led patronage and coping economies during episodes of conflict.